Hjälpsökarbeteendet hos hundar på ett hundstall - Granström, Sara (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
Dogs are known to be very good at communicating with humans and they understand human communication, this is probably a product of the domestication process. It has been shown in other studies that dogs seek help from humans when they encounter an unsolvable task, they seek help by gazing, touching or vocalizing towards the human. This help-seeking behaviour seems to vary depending on the dogs’ age, breed and forms of training. So far only one study has looked into sex-differences and found that there are differences in the breed beagle. The female dogs in that study sought more physical contact with the human. This study took place at a shelter in Sweden called Hundstallet where they take care of abandoned, abused or unwanted dogs and find new homes for them. The dogs in this study were faced with a solvable and an unsolvable problem. The purpose with the study was to see if there were any differences in males’ and females’ help-seeking behaviour and if the dogs preferred to seek help from a familiar person or an unfamiliar person. The results did not show any significant differences regarding to the sex of the dogs or the preferred human. They also did not perform other behaviours such as gaze alternation between the human and the problem, which has been seen in other studies. This may be because all the 28 dogs where too different, almost all of them where mongrels, did not live in a house with humans and some of them had been abused earlier during their life. More studies are needed in this area to fully understand the dogs’ communicative abilities.